ARITHMETIC OPERATIONS IN THE QUR’ANIC CUES TO MATHEMATICS EDUCATION - Jamhurdin Dharma, Achyar Zein, Indra Jaya (Pascasarjana UIN Sumatera Utara, 2019)
Abstract: This study aims to find out how the signs of the Qur’an against arithmetic operations in mathematicseducation, determine the urgency of arithmetic operations in the Qur’an against mathematics education,and see the relevance of arithmetic operations in the Qur’an to modern mathematics education. Themethod used in this study is qualitative in library research design, because all that wants to be investigated issourced from literature and in this study using maudhu’s interpretation. The results of the study of arithmeticoperations in the Qur’anic cues to Mathematics Education are: first, the Qur’an implies arithmetic operationsin mathematics education implicitly wherein the sum by stating the results and in subtraction, multiplicationand division only shows the part of the arithmetic operations, the existence of arithmetic operations in theQur’an as a means of human thinking in order to think mathematically. Second, the urgency of arithmeticoperations in the Qur’an for mathematics education is stated that arithmetic operations in the Qur’an arevery important for mathematics education as a means of thinking, cues for the need for innovation in learning,justification of mathematical principles, erasing thought of dichotomy in science, and as a cue forlearning mathematics. Third, the relevance of arithmetic operations in the Qur’an to modern mathematicseducation is in line with the spirit of Islamic integration in science and learning carried out by Islamic educationin this modern era. Qur’anic arithmetic operations can be material in integrated mathematics learning.The existence of arithmetic operations in the Qur’an for mathematics education is also very related in learningthe 2013 curriculum which emphasizes the scientific approach.